Effect of Vitamin D3 Supplementation to 25(OH)D, IL-17, and HbA1c Level in Pediatric Type 1 Diabetes Mellitus - Rangkuti, Rahmah Yasinta; Tjahjono, Harjoedi Adji (Journal of Tropical Life Science, 2017)
Type 1 Diabetes Mellitus (T1DM) is the consequence of autoimmune destruction process of Î² cells which associated with Th17 activity and low 25(OH)D level. This study was aimed to investigate the effect of vitamin D3 supplementation toward 25(OH)D level, Th17 activity (IL-17) and glycemic control (HbA1c) in pediatric T1DM. This study was designed as randomized clinical trials (RCT), double-blind, pre and post-test controlled study. Subject was children with T1DM who were divided into two groups: K1: subjects were treated with insulin 0.5â€“2 IU/day + vitamin D3 2000 IU/day for 3 months, K2: subjects were treated with insulin 0.5â€“2 IU/day + placebo for 3 months. Levels of 25(OH)D, IL-17 and HbA1c were evaluated after 3 months treatment using ELISA. After 3 months treatment, results showed that 25(OH)D level was significantly higher in K1 compared with K2 (p = 0.00), IL-17 level was significantly lower K1 compared with K2 (p= 0.022). Surprisingly, HbA1c level in K1 was not significantly different with K2 (p = 0.93). Furthermore, in vitamin D-treated group, 25(OH)D level was elevated significantly after 3 months treatment with vitamin D (p = 0.00), IL-17 level was reduced significantly after 3 months treatment with vitamin D (p= 0.001) Â and HbA1c level was reduced insignificantly after 3 months treatment with vitamin D (p= 0.76). Correlation study showed that there was no correlation between 25(OH)D level with IL-17 level (p= 0.160, r= -0.284) and 25(OH)D with HbA1c (p= 0.62, r= -0.10). This study can be conclude that vitamin D3 supplementation may elevate the 25(OH)D and reduce IL-17 level but did not change HbA1c level in pediatric T1DM.